Construction of the Meaning of Honesty as Social Accountability in PAD Reporting - Ritma Tri Astuthy; Alimuddin; Syarifuddin (JURNAL ECONOMINA, 2026)
This study aims to construct the meaning of honesty as a form of social accountability in reporting Regional Original Revenue (PAD) at the Regional Revenue Agency of Taliabu Island Regency. This study uses a qualitative approach with a phenomenological method. Data were obtained through in-depth interviews with three informants, namely the Head of Bapenda, the Head of Revenue Division, and the Treasurer of Bapenda Receipts of Taliabu Island Regency. Data analysis was carried out through data reduction, theme categorization, interpretation of meaning, and drawing conclusions. The results of the study indicate that honesty in PAD reporting is constructed in five main meanings, namely honesty as a match between data and facts, honesty as the courage to convey PAD realization as it is, honesty as a public mandate, honesty as a moral control mechanism, and honesty as a basis for social accountability. The research findings indicate that PAD reporting is not only interpreted as an administrative and technical process, but also as a social practice that contains moral, legal, and public responsibilities. Honesty is an important foundation in building transparency, strengthening public trust, and producing accountable regional financial information. This research contributes to the development of public sector social accounting studies by placing the value of honesty as an important element in the practice of accountability in regional financial reporting.